2001
DOI: 10.1074/jbc.m103229200
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Interactions between the Acidic P1 and P2 Proteins in the Saccharomyces cerevisiae Ribosomal Stalk

Abstract: The Saccharomyces cerevisiae ribosomal stalk is made of five components, the 32-kDa P0 and four 12-kDa acidic proteins, P1␣, P1␤, P2␣, and P2␤. The P0 carboxyl-terminal domain is involved in the interaction with the acidic proteins and resembles their structure. Protein chimeras were constructed in which the last 112 amino acids of P0 were replaced by the sequence of each acidic protein, yielding four fusion proteins, P0-1␣, P0-1␤, P0-2␣, and P0-2␤. The chimeras were expressed in P0 conditional null mutant str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
43
0
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 55 publications
3
43
0
1
Order By: Relevance
“…2D and indicate that the WT-P0 binds two copies of both P1 and P2 but that C⌬81 binds only one copy each. Considering previous evidence that P1 and P2 form a heterodimer (16,(21)(22)(23)(24) together with the present data, we infer that WT-P0, C⌬18, and C⌬55 bind two heterodimers, but C⌬65 and C⌬81 bind only one.…”
Section: Effect Of the N-terminal Deletion Of P0 On P0⅐p1-p2mentioning
confidence: 87%
See 2 more Smart Citations
“…2D and indicate that the WT-P0 binds two copies of both P1 and P2 but that C⌬81 binds only one copy each. Considering previous evidence that P1 and P2 form a heterodimer (16,(21)(22)(23)(24) together with the present data, we infer that WT-P0, C⌬18, and C⌬55 bind two heterodimers, but C⌬65 and C⌬81 bind only one.…”
Section: Effect Of the N-terminal Deletion Of P0 On P0⅐p1-p2mentioning
confidence: 87%
“…It has also been suggested that the P0⅐P1-P2 complex modulates the functional structures of the sarcin/ricin domain around 2660 as well as the 1070 regions of 23 S/28 S rRNA and makes them accessible to eukaryotic elongation factors (20). Knowledge of the molecular details on the assembly of P0, P1, and P2 proteins onto rRNA is essential to clarify protein-dependent function of the GTPase-associated center.Current biochemical and genetic evidence indicates that P1 and P2 proteins form the heterodimer (16,(21)(22)(23)(24) and P1-P2 dimers bind to a specific region within the C-terminal domain of P0 (25-27). On the other hand, the rRNA binding site seems to be located within the N-terminal region comprising about 200 amino acids (25), although direct evidence has not been shown.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…They form heterodimers (27)(28)(29), and the two P1-P2 dimers bind to neighboring sites within the C-terminal half of the L10-like stalk base protein P0 (30 -32). This pentameric P0⅐P1-P2 stalk complex can be substituted for E. coli L10⅐L7/L12 complex in the 50 S subunit and makes the ribosome accessible to eukaryotic elongation factors (33).…”
mentioning
confidence: 99%
“…In S. cerevisiae there are two P1 ( and ) and two P2 ( and ) proteins [14] and the stalk seems to be organized in preferential pairs; P1 /P2 and P1 /P2 . Again, both P1 proteins seem to be necessary for the binding of the corresponding P2 partners to P0 [15]. In T. cruzi, five components of the stalk have been identified: P0, of approximately 34 kDa, containing a Cterminal end that deviates from the eukaryotic P consensus and bears similarity with Archaea L10 protein; and four proteins of about 11 kDa (P1 , P1 , P2 and P2 ) with the typical eukaryotic P consensus sequence at their C-terminal end [16,17].…”
Section: The Ribosomal Stalk: Variable Components and Assemblymentioning
confidence: 99%